Successful activation of rat T lymphocytes by sperm specific antigens in vitro - Junko NOGUCHI; Mitsumi IKEDA; Kazuhiro KIKUCHI; Thanh Quang DANG-NGUYEN; Megumi KASASHIMA; Ken-ichiro TATEMATSU; Hideki SEZUTSU; Tadashi FURUSAWA (The Society for Reproduction and Development, 2020)
Autoimmune orchitis is a condition related to cellular immunity. A disease model involving transfer of T lymphocytes activated by known antigens would be useful for defining pathogenical molecules. Since no method for activating rat T cells using specific antigens is available, we started the study to develop the method. T cells were collected from draining lymph nodes of immunized rats, then co-cultured with syngeneic splenocytes as antigen-presenting cells (APC) in antigen-supplemented medium (= stimulation). The cells were then incubated in medium without antigens and APC (= resting). Repetitive stimulation and resting increased the number of the T cells more than 100-fold. The antigen-specific activation was demonstrated by cell proliferation assay and ELISA assay for interferon gamma. Flow cytometry revealed that > 95% of the cells expressed tumor necrosis factor alpha, a cytokine responsible for autoimmune orchitis. The present method will provide a new procedure to evaluate antigenicity of sperm molecules.